Intraoperative radiation therapy (IORT) to the tumor bed only for breast cancer - Proulx, Gary M (Radiology and oncology (Ljubljana), 2001)
Background. Recent published reports have demonstrated that not all patients with early stage breast cancer need the entire breast irradiated for local control of their disease. To address the difficulties of several weeks of irradiation treatment, investigators have utilized different radiation techniques and treatment schedules that reduce the overall treatment time without compromising outcome. Patients and methods. An analysis was made of 7 patients treated on protocol with local intraoperative radiation (IORT) alone to the lumpectomy site after surgery with or without axillary dissection. All patients received IORT with 120 kV x-rays to the tumor bed at the time of resection. Doses ranged from 1500 cGy to 2000 cGy. Three patients were stage I, two stage IIA, and two stage IIB. Results. With a mean follow up of 123 months (range 86 to 139 months), two of seven patients developed a local recurrence which were treated with mastectomy. The disease specific survival is 100% and overall survival is 86% with one patient being dead without disease. The cosmetic outcome of the 5 patients with their treated breast remaining have expressed satisfaction with the results. No treatment related complications have occurred. Conclusions. The results of our pilot study support the findings that not all patients with early stage breast cancer needthe entire breast irradiated for durable local control of their disease. However, patient numbers in this study are low and any conclusions need further evaluation with larger trials.
Keywords: breast; Breast neoplasms; dojke; Drug therapy; Intraoperative period; Mammography; neoplasm; obsevanje; radiologija; Radiotherapy; Surgery; Tamoxifen; therapy; tumor; zdravljenje